THE CORRELATION BETWEEN STUDENTS’ LISTENING ABILITY AND THEIR SPEAKING SKILL (ELang | An English Language Education Journal, 2020)
The research study entitled “The correlation between students listening ability andspeaking skill”. This correlation study done in the first semester of regular of EnglishEducation Study Program at Bale Bandung University 2019/2020 academic yearconsisted of 27 students. The research questions of this research (1) Is there anycorrelation between students’ listening ability and their speaking skill? (2) If there iscorrelation it is high, moderate, and low? To answer the research, the researcher usedPearson Product Moment. It was found that the derived t = 5.071 is greater the tablecritical value of t = 2.060, at p = .05 with df = 25 (5.071>2.060). It was proved by theresult of the analysis that the r value is 0.213. The result of this research showed thatthere correlation between students’ listening ability and their speaking skill. And thecorrelation is low between students listening and speaking skill.